Functional Train Algebras of Rank ≤ 3 - Bayara, Joseph; Coulibaly, Siaka (Contemporary Mathematics, 2024)
In this paper we show that every baric algebra satisfying a functional train identity of rank ≤ 3 and admitting an idempotent is a special train algebra. The functional train equation of train algebras of rank 3 is given. Some examples are also given.